2011
DOI: 10.1093/schbul/sbr077
|View full text |Cite
|
Sign up to set email alerts
|

The 5-Year Course of Obsessive-Compulsive Symptoms and Obsessive-Compulsive Disorder in First-Episode Schizophrenia and Related Disorders

Abstract: The 5-year course of OCS/OCD in patients with first-episode schizophrenia or related disorders is variable. OCS/OCD comorbidity was not associated with a more severe course of psychotic symptoms and relapse. Comorbid OCD was associated with more severe depressive symptoms, social dysfunction and worse premorbid functioning. Specific treatment options for schizophrenia patients with comorbid OCD are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
91
3
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 43 publications
11
91
3
6
Order By: Relevance
“…In fact, the few studies about this topic maintained a categorical approach (sub-threshold OCS vs full-blown OCD) [10,11].…”
Section: Sofas Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the few studies about this topic maintained a categorical approach (sub-threshold OCS vs full-blown OCD) [10,11].…”
Section: Sofas Scoresmentioning
confidence: 99%
“…The reason underlying the discrepancy across studies has been related to a phase-dependent effect of OC dimension on level of functioning, i.e., protective in early stages and deleterious in the later phases of the illness [9]. More recently, a 5-year follow-up study [10] has suggested that the severity of OC features might differentially impact social functioning in schizophrenia, with sub-threshold symptoms showing an improving effect and full-blown OCD a worsening one: Among patients with schizophrenia, those with OCS showed a better social functioning than both patients without OCS and with OCD. By contrast, a previous crosssectional study [11] found no significant differences in social functioning between schizophrenia patients with OCS and OCD.…”
Section: Introductionmentioning
confidence: 99%
“…In the current case, the patient was observed for improvement on the changed antipsychotic medication. A study [3] describes comorbid OCD with schizophrenia. In this, they mention that OCD was associated with more severe depressive symptoms, social dysfunction and worse premorbid functioning.…”
Section: Case Presentationmentioning
confidence: 99%
“…Bir çalışmada şizofreni, şizofreniform bozukluk ve şizoaffektif bozukluk tanısı konan olgular beş yıl boyunca izlenmiş ve farklı değerlendirmelerde obsesif kompulsif belirtilerinin görülme oranının %22.7-30.6 arasında, obsesif kompulsif bozukluk tanısının %7.3-11.8 arasında değiştiği saptanmış ve bu birlikteliği açıkladığı düşünül-müştür. 17 …”
Section: İstatistiksel Değerlendirmeunclassified